Could the U.S. Energy Sector Become New Engine For Growth? - Zajicek, Edward K.; Karagiannis, Nikolaos; Wilhoit, Thomas (International Journal of Energy Economics and Policy, 2016)
The intent of this paper is to discuss the U.S. energy sector in the context of economic growth, employment conditions, manufacturing competitiveness, and trade deficits. The paper carefully examines how utilization of domestic energy resources can strengthen the United States economic position in both domestic and foreign markets. Consideration is given to expanding the use of domestic energy resources to improve competitiveness in the global goods market and reduce dependency on foreign oil. In particular, the sections of the paper discuss: the current U.S. macroeconomic situation with an emphasis on economic growth and labor market; domestic oil and gas production; energy security; institutional arrangements necessary to deliver reliable U.S. energy resources to domestic and foreign markets; and policy considerations deemed necessary to boost energy growth. Keywords: Economic growth, Energy consumption, Energy production, development policy JEL Classifications: O; Q